Enzalutamide-resistant castration-resistant prostate cancer: challenges and solutions - Tucci, Marcello (Onco Targets Ther, 2018)
The new-generation hormonal agent enzalutamide has been approved for the treatment of metastatic castration-resistant prostate cancer (CRPC), in both post- and predocetaxel setting, due to the significant improvement in overall survival. More recently, enzalutamide also showed impressive results in the treatment of men with nonmetastatic CRPC. Unfortunately, not all patients with CRPC are responsive to enzalutamide, and even in responders, benefits are limited by the development of drug resistance. Adaptive resistance of metastatic prostate cancer to enzalutamide treatment can be due to the activation of both androgen receptor (AR)-dependent pathways (expression of constitutively active AR splice variants, AR point mutations, gene amplification and overexpression) and mechanisms independent of AR signaling pathway (altered steroidogenesis, upregulation of the glucocorticoid receptor, epithelial–mesenchymal transition, neuroendocrine transformation, autophagy and activation of the immune system). In this review, we focus on resistance mechanisms to enzalutamide, exploring how we could overcome them through novel therapeutic options.